THE ROLE OF TEACHERS IN FACING ACADEMIC PROCRASTINATION AS AN EFFORT TO DISCIPLINE ELEMENTARY SCHOOL STUDENTS' LEARNING - Amalia Farizkya Ananda; Ratnasari Diah Utami (Jurnal Cakrawala Pendas, 2023)
Assignments are one of the strategies that teachers employ to teach students how to become disciplined and responsible individuals. However, many students procrastinate in their studies, which prevents them from developing independent, disciplined, and responsible traits, as outlined in the Pancasila Student Profile. The research objectives encompass the following: first, identifying the causes of academic procrastination among students. Second describing the attitudes of teachers towards addressing academic procrastination. Third, examining the efforts made by teachers in fostering discipline in student learning. The research methodology employed is qualitative research, utilizing interviews, observations, and documentation as the primary methods for data collection. The research subjects consisted of students in grades IV and V who exhibited procrastination tendencies, as well as teachers in the same grade levels. The data analysis process involved three steps: data reduction, data presentation, and drawing conclusions. The research findings reveal the following: There are two types of factors, internal and external, that contribute to student procrastination. Teachers adopt various approaches to address academic procrastination, such as approaching students, providing motivation or guidance, implementing punishment or rewards, and diversifying teaching methods. Teachers take specific steps to foster discipline in learning, such as establishing class agreements, organizing positive activities, and implementing punishment or rewards. Hence, teachers play a crucial role in implementing strategies aimed at reducing procrastination and cultivating a disciplined, independent, and responsible attitude among students. Tugas adalah salah satu strategi yang guru gunakan untuk mengajarkan siswa menjadi pribadi yang disiplin dan bertanggung jawab. Akan tetapi banyak siswa yang melakukan prokrastinasi didalam pembelajaran sehingga, tidak menanamkan karakter mandiri, disiplin, dan bertanggung jawab sesuai dengan Profil Pelajar Pancasila. Tujuan penelitian meliputi pertama, mengidentifikasi penyebab prokrastinasi akademik pada siswa. Kedua, mendeskripsikan sikap guru dalam menghadapi prokrastinasi akademik. Ketiga, upaya guru dalam pendisiplinan belajar siswa. Metode penelitian menggunakan penelitian kualitatif. Wawancara, observasi, dan dokumentasi adalah metode yang digunakan untuk pengumpulan data. Subjek penelitian siswa kelas IV dan V yang melakukan prokrastinasi serta guru kelas IV dan V. Tiga langkah uji analisis data adalah reduksi data, penyajian data, dan penarikan kesimpulan. Temuan penelitian menunjukkan bahwa penyebab siswa melakukan prokrastinasi ada dua jenis faktor internal dan eksternal; sikap guru dalam menghadapi prokrastinasi akademik yaitu dengan melakukan pendekatan terhadap siswa, memberikan motivasi atau nasihat, memberikan punishment atau reward, dan memvariasi cara mengajar; langkah yang dilakukan guru dalam pendisiplinan belajar yaitu membuat kesepakatan tiap kelas, melakukan kegiatan posistif, adanya punishment atau reward. Oleh karena itu, guru memiliki peran penting dalam penerapan langkah-langkah agar prokrastinasi mampu berkurang dan siswa memiliki sikap disiplin, mandiri, dan tanggungjawab.